Scalable van der Waals graphene films for electro‐optical regulation and thermal camouflage - Ziqi Li; Xujiang Chao; Andrew Balilonda; Wei Chen (InfoMat, 2023)
Abstract Graphene exhibits enormous advantages in mid‐infrared (MIR) regulation because of the active control, precise regulation, and large modulation depth. Such graphene films are prepared via chemical vapor deposition (CVD) or reduction, which cannot realize large‐scale production and limit the applications. Graphene films with van der Waals (vdW) structure enable excellent mechanical and electrical performance for flexible electrodes and electronics and might be a candidate for MIR regulation. However, current techniques for preparing vdW graphene films require binder or solution assistance, resulting in chemical residues and performance degradation. Here, a new strategy for preparing large‐area vdW graphene films by simple mechanical adhesion without any additives was proposed. By selecting the carriers and substrates with proper fracture energies, graphene nanosheets can be transferred from one polymer to another with a layer‐by‐layer structure. The obtained graphene films possess desired thickness and comparable electrical conductivity (92.8 ± 4.6 ohm sq–1) with those by chemical vapor deposition. They are of high compactness even for ions to intercalate reversibly, which exhibit excellent electrochemical activity and electro‐optical regulation capability, effectively suppressing 90% thermal radiation. This strategy can be extended to prepare high‐performance vdW graphene films on various polymer substrates and used for sustainable and smart electro‐optical applications.